Analisis Perbandingan Kinerja Algoritme Dijkstra, Bellman-Ford, dan Floyd-Warshall Untuk Penentuan Jalur Terpendek Pada Arsitektur Jaringan Software Defined Network - Aprillia Arum Pratiwi; Widhi Yahya; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software defined network (SDN) is a centralized and flexible network concept compared to traditional networks that exist today. SDN has been developed in the last few years and has been widely implemented, one of which is routing networks. Routing is the process of finding the communication path used to send packets from the sender to the recipient. The implemented routing algorithm is tasked to determine the shortest paths, namely Dijkstra, Bellman-Ford, and Floyd-Warshall algorithms. The three algorithms will be implemented using the Mininet and Ryu controller emulators. For determining the path required the determination of the link or cost weight. Cost in this study is based on the calculation of the reference bandwidth of 1000 Mbps and the bandwidth link that uses three types of capacity quantities, namely 10 Mbps, 100 Mbps, and 1000 Mbps. Testing is done with parameters, namely validation, convergence time, throughput, recovery time and packet loss. Based on the results of validation, the system runs according to the calculation of the manual calculation of each algorithm. In convergence time testing, Dijkstra was superior with an average of 0.0087 seconds compared to Bellman-ford 0.0094 seconds and Floyd-Warshall 0.02025 seconds. In testing the three throughput algorithms do not have far distinction. Based on recovery time testing, the Floyd-Warshall algorithm has faster recovery time than other algorithms. Based on the testing of packet loss Dijkstra is still superior in handling packet loss when sending.